A novel method to prepare a nanotubes@mesoporous carbon composite material based on waste biomass and its electrochemical performance. Issue 8 (30th January 2017) - Li, Huanxin; Gong, Yi; Fu, Chaopeng; Zhou, Haihui; Yang, Wenji; Guo, Meilin; Li, Mengbo; Kuang, Yafei
Abstract : Hierarchical nanotubes@mesoporous carbon composite materials were controllably synthesized by an innovative method based on plant waste corncob and nitrogen source melamine via thermal treatment. Abstract : Hierarchical nanotubes@mesoporous carbon composite materials were controllably synthesized by an innovative method based on plant waste corncob and nitrogen source melamine via thermal treatment. The corncob provides both a carbon source and a small amount of Fe as the catalyst, while melamine offers a nitrogen source. Corncobs were firstly pretreated with concentrated sulfuric acid and then mixed with melamine. After calcination at 800 °C for 2 hours, a new composite carbon material with a unique structure with a large amount of thin walled nitrogen-doped carbon nanotubes orderly and vertically growing on the mesoporous carbon frame was obtained. The diameter of nanotubes is ∼50 nm while their length varies from 0.1–20 μm, which could be controlled by adjusting the ratio of pretreated corncob to melamine. Meanwhile, the composite material possesses stable interconnected pores and channels with a high surface area of 1100 m 2 g −1, which significantly accelerated the transfer rates of ions and electrons. The electrochemical test results demonstrated that this composite material exhibits a superior capacitance of 538 F g −1 in an aqueous electrolyte and 320 F g −1 in an organic electrolyte at a current density of 1 A g −1 . The specific capacitance of the composite material remained up to 90% of the initial value after 10 000 cycles, showing excellent long-term cycling stability. For lithium sulfur battery application, the composite material as a sulfur host delivered an initial capacity of 1047 mA h g −1, and exhibited a relatively stable cycling performance, maintained a capacity of 682 mA h g −1 for 300 charge/discharge cycles at 0.5C. The structure, morphology and growth mechanism of the composite material were also analyzed and discussed in detail.